Kedudukan Konsultan Hak Kekayaan Intelektual Serta Kebijakan HKI - Azed, Abdul Bari (UI Scholars Hub, 2005)
Intellectual property right has become important issue for developing countries, especially Indonesia. The governing law for intelelctual property right not only protects the inventors but also the products of intellectual property. Recently, the Government Law No. 2 Years 2005 concerning Consultant of Intellectual Property Rights. This Act is enacted to implement the prescribed article in the Law of the Intellectual Property Rights which required further regulations on Consultant of Intellectual Property Rights. This article will discuss further the issue of IPR Consultant’s role in regards to Indonesian IPR policy.